Perinatal testicular torsion diagnosed as an intraperitoneal mass: case report and literature review - Huang, Cheng; Ma, Yan; Bai, Dongsheng; Hao, Chunsheng (Frontiers in Pediatrics, 2025)
Perinatal testicular torsion is not common in clinic. We report our experience in treating such a condition in a 50-day boy with an intraperitoneal mass. The clinical manifestations, physical examination, imaging examination and treatment of the boy were retrospectively analyzed and the related literatures were reviewed. Laparoscopic exploration, resection of abdominal mass, high ligation of left processus vaginalis and left orchiopexy were performed after admission. According to the results of intraoperative frozen-section examination and paraffin section after operation, combined with the history of children, consider the diagnosis of “right cryptorchidism with perinatal testicular torsion”. We reported the case for the purpose of exploring the characteristics, diagnosis, differential diagnosis and treatment of perinatal testicular torsion (Perinatal testicular torsion, PTT), and improving the understanding of cryptorchidism with perinatal testicular torsion.